The Modern Literary (After)lives of al-Khiḍr. Issue 3 (October 2014) - Toorawa, Shawkat M.
<x xml:space="preserve">Abstract</x> Prominent examples of major Qur'anic characters in modern world literature include Joseph (and Zulaykha) -like characters in the 1984 Arabic novel, al-Rahīna (The Hostage) by the Yemeni writer Zayd Muṭīʿ Dammāj (d. 2000) and the fictionalised portrayal of the women around the Prophet Muḥammad in Algerian filmmaker and novelist Assia Djebar's 1991 French novel, Loin de Médine (Far from Medina). In this article I focus, rather, on a 'minor' Qur'anic character, al-Khiḍr (cf. Q. 18:65–82). I begin by looking briefly at the evolution of al-Khiḍr in Islamic literatures generally and then focus on his deployment in several short fictional accounts, viz. the 1995 French novella L'homme du livre (Muhammad, A Novel) by Moroccan author Driss Chraïbi (d. 2007); Victor Pelevin's 1994 Russian short story, 'Prints Gosplana' (Prince of Gosplan); the 1998 short story, 'The Mapmakers of Spitalfields', by Bangladeshi-British writer Manzu Islam; and Reza Daneshvar's 2004 Persian tale, 'Mahboobeh va-Āl' ('Mahboobeh and Ahl'). I characterise the ways in which these modern authors draw on the al-Khiḍr type, persona, and legend, and go on to suggest how and why the use of al-Khiḍr in modern literature is productive and versatile.